BACTERIOLOGICAL QUALITY OF UNPACKAGED POWERED MILK SOLD WITHIN KADUNA - Moroof, M. B.; Yunus, S. I.; Momoh, L. (FUDMA JOURNAL OF SCIENCES, 2023)
Milk is a nutritious food and a excellent source of protein needed for growth and body building. It’s costly nature however makes it unaffordable by most people especially in a developing country like Nigeria. The aim of this study is to evaluate the bacteriological quality of unpackaged powdered milk sold within Kaduna south local government. The objectives are to determine the bacteriological load of three brands of powdered milk and to isolate and identify bacteria from the samples analyzed. This was done using standard microbiological methods. Thirty milk samples from three different brands (A, B and C) were collected from markets within Kaduna south local government. The bacterial load of brand A ranged from 1.26x 105_ 7.0x105 with a mean viable count of 4.0x105 ± 2.9 that of brand B ranged from 1.38x105-2.44x105 with a mean count of 2.0x105 ± 0.5 while that of brand C ranged from 1.00x105-2.0x105 with a mean count of 1.3x105±0.5.Three genera of bacteria (Bacillus spp Staphylococcus aureus, and Streptococcus spp) with percentage occurance of 60, 23.3 nd 16.7% respectively were isolated from all the milk samples analysed. The study establish evidence of contamination of all the milk samples with the total viable count in all the samples(>104 CFU/ g). Proper hygienic practices should be enforced and maintained during handling to reduce post pasteurization contamination and spoilage of powdered milk.